Effect of Supplementation Level of Leucaena Leaves and Wheat Bran to Grass Based Diet on Milk Yield and Cost of Production in Dairy Goats - Brenda Jemutai Kiptui; Eunice Akello Mewa; Jackson Kibet Kitilit (International Journal of Scientific Research in Science and Technology, 2025)
Leucaena (Leucaena leucocephala) is a forage of arid and semi-arid rangeland. It is a high protein forage that is drought tolerant and resistant to pests and diseases. Leucaena provided palatable, digestible and nutritious forage for ruminants thus helps to improve milk yield. Wheat bran is an excellent feed for goats due to its high palatability and laxative properties. The problem encountered was low milk production among dairy goat farms at the study area. Goat milk production has the potential to increase food security. An experiment was designed to study the effect of supplementing dried leucaena and wheat bran mixture on milk yield and the cost of its production in dairy goats at Mogotio Sub-County, Baringo County. This experiment was carried out on one farm where supplementations were carried out twice a day and milking done once daily. The study used Latin square design with five treatments of increasing levels of supplementation at control, 5, 10, 15, and 20% of the diet. The experiment was run for 35 days using 5 lactating dairy goats of body weights ranging between 35 and 53kg. The parameters observed included milk yield and cost of the feeds. The data was analysed using analysis of variance and significant means were separated using tukey’s test. Results showed that dairy goats on supplementation produced more milk compared to the control. Supplementation treatment four had the highest milk production (476ml). Cost of dried leucaena leaves mixed with wheat bran was lower than commercial concentrates. In conclusion, linear increase in milk yield on all the treatments containing increasing levels of supplementation of dried leucaena leaves mixed with wheat bran at a fairly low cost was observed. The farmers should plant more leucaena and be trained to formulate treatment three diet for high milk production from lactating dairy goats.
Keywords: Commercial concentrates; Fodder; Goat products; Lactating goats; Milk production